Analysis of a Building Structure Under Seismic Load Using Base Isolation Technique in Analysis Tool A Review - Chourasia, Ankit Thakur; Chourasia, Rahul Satbhaiya; Chourasia, Murlidhar Chourasiya (International Journal of Scientific Research in Civil Engineering, 2024)
Safety of people in a building depends on capability of the building to resist earthquake waves and then stands upright after earthquake situation without or with few damages and maintenance. Various systems like dampers, base isolators, shear wall, elevated water tank, etc., are used to dissipate seismic energy. Effectiveness of these systems is based on its type and position of these elements. In this paper, we are conducting research on “base isolators”.